Reflections about education, memory and human rights (International Journal of Scientific Research and Management (IJSRM), 2024)
Education, memory, and human rights form the subject of this research article in order to evaluate the critical role of education practice in recalling and enhancing human rights. In totality, the research brings into focus the significance of education when it comes to explaining history, self, and the world within which we live through the evaluation of ancient and current case studies. This article focuses on the exploration of notions relating to human rights education, including its objectives and approaches, as well as the effects of the implementation of human rights education in societies. By using examples of HRE implementation in Germany, South Africa, and Chile, it explains successful practices and impacts on the culture of remembrance and human rights. The article also covers the difficulties of providing good HRE, including lack of resources, political impetus, and, to some extent, the assimilation needs of teachers. Based on the analysis of the current status of HRE programs, it provides valuable suggestions for the improvement of HRE programs globally and especially stresses the acknowledgement and support from the international community and organizations. This research notes that the practice of disseminating human rights information for curricula in various countries across the globe remains vital in making the next generation of leaders agents of justice and equality, hence enhancing justice in society.